Beautiful Cycles : A Theory and a Model Implying a Curious Role for Interest - Gross, Marco (IMF Working Papers; Working Paper ;, 2021)
Where do economic cycles come from? This paper contemplates an utmost minimalistic model and underlying theory that rest on two assumptions for letting them emerge endogenously: (1) the presence of interest-bearing debt; and (2) a degree of downward nominal wage rigidity. Despite its parsimony, the model generates well-behaved, self-evolving limit cycles and replicates six essential empirical facts: (1) booms are long- while recessions short-lived; (2) leverage is procyclical; (3) firm profit and wage shares in GDP are counter- and procyclical, respectively; (4) Phillips curves are downward-sloping and convex, and Okun's law relation is replicated; (5) default cascades arise endogenously at the turning points to recessions; (6) lending spreads are countercyclical. One can refer to the model as being of a Dynamic Stochastic General Disequilibrium (DSGD) kind.